RETRACTED: Implementing energy-saving technologies in hot asphalt production: A comprehensive review - Sarmonov Azizbek; Rustamov Kamoliddin (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001